Upaya Meningkatkan Efisiensi Bahan Baku Dengan Menggunakan Pendekatan Economiq Order Quantity Studi Kasus Pada CV. Luthfi Jaya Abadi Desa Trisnomulyo Lampung Timur - Suryadi, Suryadi; Septiana, Nani; Fakhri, Lutfhi Faisal (Universitas Muhammadiyah Metro, 2023)
Tapioca production is a business that is engaged in the field of basic needs that focuses on the production of tapioca flour with the marketing area of ​​Lampung Province in general and Central Lampung Regency in particular. The main raw material used in the production process is cassava which is obtained from collectors and farmers directly. So the purpose of this research is to find out 1) the number of orders/purchases that must be made by the cassava factory in 2017-2020 (Economic Order quantity), 2) the supply of raw materials that must be determined at the cassava factory in 2017-2020 (Safety Stock), 3 ) the cost to determine the reorder of cassava rows in 2017-2020 (Reorder Point), 4) the cost of the total amount needed to determine the calculation at the cassava factory in 2017-2020 TIC (Total Inventory Cost). This type of research uses quantitative methods. Sources of data used in the form of secondary data relating to the supply of raw materials in CV. Luthfi Jaya Abadi, Trisnomulyo Village, Batanghari Nuban District, East Lampung Regency 2017-2020. The research results prove that 1) The most economical purchase in 2017 using the Economic Order Quantity method is 360 tons with a purchase frequency of 833 times in one year. Whereas in 2018 it was 400 tons with a purchase frequency of 15 times a year, for 2019 it was 240 tons with a purchase frequency of 7 times in one year, and in 2020 it was 1,200 tons with a purchase frequency of 29 times in one year. 2) Calculation that the standard storage of raw material usage in 2017 is 6.52 tons, while the Safety Stock for 2017 is 10.75 tons. Then the results in 2018 for the calculation of standard storage of raw material use in 2018 were 0.388 tons, while the Safety Stock for 2018 was 0.640 tons. For 2019, the calculation result of standard storage of raw material usage in 2019 was 0.687 tons, while the Safety Stock for 2019 was 1.133 tons and the last calculation results of Standard storage of raw materials usage in 2020 was 26.99 tons, while the Safety Stock for 2020 amounting to 44.53 tons. 3) From the results of the ROP (Re Order Point) in 2017 the reorder achievement was 10,041 tons, in 2018 it was 42,125 tons, in 2019 it was 39,125 tons and in 2020 it was 42.194 tons. 4) In 2017 obtained TIC based on calculations using the EOQ method of Rp. 1,041,666,250,-, for the following year, 2018 the TIC is Rp. 4,218,750, -, next year 2019 the results of the calculations obtained TIC results of Rp. 4,000,000, - and the next in 2020 will get Rp. 2.125.000,- from the calculation of TIC.